PENERAPAN PRINSIP 5P DALAM MEMINIMALISIR RISIKO PEMBIAYAAN MUSYARAKAH MUTANAQISAH PADA PT. BANK NTB SYARIAH - Mareta, Hany; Hariono, Hariono; Susanti, Nurul (Faculty of Islamic Economics and Business, 2022)
The purpose of this study is to find out how to apply the 5P principle (party, purpose, payment, profitability, protection) in minimizing the risk of providing musyarakah mutanaqisah financing and find out whether or not the application of the 5P principle is effective in minimizing financing risk. This research uses a qualitative approach and by researching directly at PT. Bank NTB Syariah. This type of research data uses primary and secondary data types, data collection techniques through observation, interviews, and documentation. The informant came from the consumer finance division and risk management desk. The result of this study is the application of the 5P principle in minimizing the risk of providing musyarakah mutanaqisah financing at PT. Bank NTB Syariah has been applied according to theories on every principle and has applied the precautionary principle as in Law No.21 of 2008 concerning Sharia Banking in Article 2 and Article 23 paragraphs (1) and (2), and Bank Indonesia Regulation No.14 of 2012 concerning Asset Quality Assessment of Commercial Banks, in Article 2 paragraphs (1) and (2). Then the effectiveness of the application of the 5P principle in 2019 to 2021 has been very effective in minimizing the risk of musyarakah mutanaqisah financing, this is based on the results of interviews and observations from Non-Performing Financing which is decreasing and the bank can achieve the Non Performing Financing target contained in the Bank's Business Plan in 2019 to 2021